Prophylaxis of Imune Deficiencies and Neonatal Diarrhea Syndrome among Sucking Piglets by Administration of Organic Selenium (Sel-Plex) (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: milking swine; neonatal diarrhea; profilaxy; sucking piglets; sel-plex